Sains Islam: Sebuah Refleksi Metodologis dan Implementasinya di Sekolah Alam Bukittinggi - Annisa, Ana Citra; Yahya, Anandita (Lembaga Yasin AlSys, 2025)
The divide between secular scientific approaches and Islamic spiritual values remains a persistent challenge within formal education systems, where full integration has yet to be realized. This study aims to reflect on the methodological approach to Islamic science and examine its implementation at Sekolah Alam Bukittinggi. Using a descriptive qualitative method, data were collected through field observations, in-depth interviews with teachers and school administrators, documentation of learning activities, and a literature review related to Islamic science. The findings indicate that: (1) Islamic science is a discipline integrated with religious values, based on a tripartite structure encompassing the microcosm (subject), macrocosm (object), and metacosm (spiritual realm). Epistemologically, Islamic science offers a broader scope than Western science by encompassing both physical and metaphysical dimensions, emphasizing the search for meaning behind natural phenomena as advocated by Muslim philosophers. (2) Sekolah Alam Bukittinggi applies a holistic approach that integrates modern science with the values of tawḥīd, ethics, and the concept of human stewardship (khilāfah) over nature. The learning process is contextual and application-oriented, utilizing the environment as a natural laboratory while emphasizing Islamic values such as gratitude, ecological responsibility, and viewing nature as a sign of God's greatness. This study concludes that the integration of Islamic science in education can be effectively realized through contextual, value-based pedagogical approaches.